Leading the Blind: A Critical Look at Visible Learning - Johnson, Greg R.; Janzen, Melanie D. (Critical Education, 2023)
In 2009, John Hattie’s book Visible Learning: A Synthesis of over 800 Meta-Analyses Relating to Achievement brought big data to education. In the decade and a half since Visible Learning was originally published it has been aggressively marketed and has now grown into a large suite of branded books, tools, and products. Visible Learning continues to exert influence over educational thinking, policy design, and decision making. This critical essay probes the foundations of Visible Learning, seeking to better understand the work’s significance. Criticism is leveled at the methodology, positionality, capitalistic motivations, and mischaracterization of science underpinning the book and the subsequent franchise that has grown from it. The essay argues that the philosophy of education represented by Visible Learning resides within a reductive neoliberal ideology that pushes problematic reform, demands unreasonable accountability, and promotes the de-professionalization of teachers.